2018
DOI: 10.13189/ujer.2018.060415
|View full text |Cite
|
Sign up to set email alerts
|

Student Perceptions on Collaborative Writing in a Project-based Course

Abstract: The traditional view that writing is an individual activity often translates into the teaching of it as an individual task. Rarely do students engage in extensive dialogue with their peers when writing. However, much writing in the workplace takes place in collaboration with others. Although, on the surface, many authors may not seem to write with others collaboratively, the truth is that they engage in intensive intrapersonal community affected by interpersonal communication. They also communicate with them t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 11 publications
2
44
0
1
Order By: Relevance
“…This is the point in writing and learning community is the right place for them to learn. Shi and Yang (2013); Wilmot and Sioux (2018); Liu, Pardo, and Liu (2017); Dean and Warren (2012) ;Chang, Rao, Stewart, Farley, and Katherine (2016); Deveci (2018);and Schwehm, Saxton, and Stuckey (2017) in their researches state clearly that learning community in different approach gives the extraordinary effect for moving the learners in writing.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is the point in writing and learning community is the right place for them to learn. Shi and Yang (2013); Wilmot and Sioux (2018); Liu, Pardo, and Liu (2017); Dean and Warren (2012) ;Chang, Rao, Stewart, Farley, and Katherine (2016); Deveci (2018);and Schwehm, Saxton, and Stuckey (2017) in their researches state clearly that learning community in different approach gives the extraordinary effect for moving the learners in writing.…”
Section: Discussionmentioning
confidence: 98%
“…The instructor's attendance in this engagement and community has the main role to facilitate the learners to be more active and it seems that there are no constraints and barriers because all learners have the same goal to learn. Deveci (2018) states that collaborative writing experience is something positive for shaping the learners' motivation in learning. It contributes to English language and teamwork skill in writing that is sharpened.…”
Section: Methodsmentioning
confidence: 99%
“…Emiratis' use of the English language for various purposes has been investigated by researchers in such areas as writing (Deveci 2018, Nunn, Deveci & Salih 2015, Al Murshidi 2014), speaking (Al Nawrasy 2013, Khameis 2007, and listening (Barlow 2009). However, their realization of speech acts has received little interest from researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Alharbi (2019) indicated that Google Docs could facilitate writing instructional practices, especially for collaborative writing activities. Google Docs allows people to work, read, review, comment, and edit to each other in the same document simultaneously (Deveci, 2018;Ishtaiwa & Aburazeq, 2015). Given the perpetual benefits that Google Docs offers, this study reported in the paper sought to explore students' interactions and peer feedback practices during the collaborative writing processes using Google Docs, especially in generating their ideas, organizing the text, and constructing the sentences.…”
Section: Introductionmentioning
confidence: 99%